L’engagement des enseignants dans des dispositifs pédagogiques : une traduction entre prise de risques et paris adjacents - Quentin Magogeat (Recherches en Éducation)
This article focuses on the reasons for teachers commitment in two pedagogical devices prescribing forms co-teaching (the “More teachers than classes” and a co-teaching device in eleven one-class rural Ardèche in mountain schools). By mobilizing actor-network theory, we analyze the different stages of the translation processes which led teachers to engage in the implementation of these devices. It then appears, beyond the local translations made by the actors, that the commitment of the latter is based on several interests in co-teaching and adjacent bets more or less constraining.